2022
DOI: 10.1002/advs.202203234
|View full text |Cite
|
Sign up to set email alerts
|

Facilely Achieved Self‐Biased Black Silicon Heterojunction Photodiode with Broadband Quantum Efficiency Approaching 100%

Abstract: Photodiodes are fundamental components in modern optoelectronics. Heterojunction photodiodes, simply configured by two different contact materials, have been a hot research topic for many years. Currently reported self‐biased heterojunction photodiodes routinely have external quantum efficiency (EQE) significantly below 100% due to optical and electrical losses. Herein, an approach that virtually overcomes this 100% EQE challenge via low‐aspect‐ratio nanostructures and drift‐dominated photocarrier transport in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…4E ) is compared with the EQE for an annealed device at 0 V in fig. S14 ( 58 ). For the unannealed devices in this work, there is a limited chemical passivation effect at the surface, while the annealed device shows excellent surface chemical passivation ( 58 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4E ) is compared with the EQE for an annealed device at 0 V in fig. S14 ( 58 ). For the unannealed devices in this work, there is a limited chemical passivation effect at the surface, while the annealed device shows excellent surface chemical passivation ( 58 ).…”
Section: Resultsmentioning
confidence: 99%
“…S14 ( 58 ). For the unannealed devices in this work, there is a limited chemical passivation effect at the surface, while the annealed device shows excellent surface chemical passivation ( 58 ). In our previous work, it is demonstrated that a wide depletion region and a well chemically passivated surface enable a nearly complete collection of broadband photocarriers at 0 V bias ( 58 ).…”
Section: Resultsmentioning
confidence: 99%
“…While MACE has previously been applied to Schottky photodiodes [26], [27], it is well known that they always suffer from high dark current and, consequently, have limited sensitivity. For instance, Zhang et al [26] have recently reported a high-responsivity MACE Si Schottky photodiode; however, the achieved dark current density is as high as 130 nA cm −2 at −1-V bias, which cannot compete with commercial Si photodiodes (typically <10 nA cm −2 ). Unlike Schottky diodes, p-n diodes are known for their low dark currents.…”
Section: Introductionmentioning
confidence: 99%
“…A diverse range of measures, including on-silicon lead-free halide perovskite single-crystalline thin film (SCTF), nanostalagmite structures, Ge nanowires, grating structures, graphene interlayer, reflector mirror, and tensile strain, have been investigated to enable high-performance photodetectors [ 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. Of them, tensile strain is considered an effective measure to enhance the optical properties of Ge [ 15 ].…”
Section: Introductionmentioning
confidence: 99%